1996
DOI: 10.1029/95gl03779
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the removal of gaseous HNO3 inside the arctic polar vortex in January 1992

Abstract: Unexpectedly low column amounts of HNO3 (1.3×1016 cm−2) inside the Arctic polar vortex were obtained on January 9, 1992 by airborne FTIR emission measurements. After correction for dynamic variations it is concluded that about 40% of the column HNO3 had been removed from the gas phase. The observed depletion is consistent with a nearly equilibrium saturation of HNO3 over nitric acid trihydrate. It cannot be explained by the uptake of HNO3 in ternary H2SO4/H2O/HNO3 mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The frost point temperatures of nitric acid vapor on the surface of NAT and water vapor on the surface of ice are estimated, under the assumed atmospheric condition that mixing ratio of HNO3 and 1120 are 10, 5, 1 ppbv and 5, 3 ppmv respectively, on the basis of the laboratory experiments by Hanson andMauersberger (1988), Jaecker-Voirol et al (1990), and Luo et al (1995). These values are referred from observational values of stratospheric water vapor (e.g., Kelly et al, 1990;Pruvost et al, 1993;Overlez and Overlez, 1994), and of nitric acid vapor (e.g., Clarmann et al, 1993;Oelhaf et al, 1994;Murcray et al, 1994;Hofner et al, 1996). From the temperature distributions, it is suggested that stratospheric temperature decreased the expected threshold temperature of PSCs (Type I) formation in those days.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…The frost point temperatures of nitric acid vapor on the surface of NAT and water vapor on the surface of ice are estimated, under the assumed atmospheric condition that mixing ratio of HNO3 and 1120 are 10, 5, 1 ppbv and 5, 3 ppmv respectively, on the basis of the laboratory experiments by Hanson andMauersberger (1988), Jaecker-Voirol et al (1990), and Luo et al (1995). These values are referred from observational values of stratospheric water vapor (e.g., Kelly et al, 1990;Pruvost et al, 1993;Overlez and Overlez, 1994), and of nitric acid vapor (e.g., Clarmann et al, 1993;Oelhaf et al, 1994;Murcray et al, 1994;Hofner et al, 1996). From the temperature distributions, it is suggested that stratospheric temperature decreased the expected threshold temperature of PSCs (Type I) formation in those days.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Gao et al (2001) have highlighted the importance of denitrification for Arctic ozone depletion; Höpfner et al (1996) observed the removal of gaseous HNO 3 in the Arctic vortex in 1992 by airborne infrared emission spectroscopy. Moderate large-scale denitrification was observed in the polar Arctic spring 2000 by UARS MLS (Santee et al, 2000), while Popp et al (2001) report strong denitrification, inferred from in situ measurements.…”
Section: The Arcticmentioning
confidence: 99%